Phototaxis of synthetic microswimmers in optical landscapes - Celia Lozano; Borge ten Hagen; Hartmut Löwen; Clemens Bechinger (Nature Communications, 2016)
The capability to move towards or away from light sources, namely phototaxis, is an essential feature of many microorganisms like bacteria or motile cells. Lozano et al. show an artificial phototaxis system that enables autonomous navigation of colloidal Janus spheres in a laser-generated light landscape.